Enfermedades que afectan al cultivo de Mango (Mangifera indica L.) y su control preventivo, en Ecuador - Bricio Morejón, Itati Dayanna (2021)
This document dealt with the identification of the diseases that affect the Mango (Mangifera indica L.) crop and their preventive control, in order to increase yields. The main problem that affects mango plantations are diseases caused by fungi, because they attack especially in the flowering season, causing the flowers not to open and fall, therefore causing significant drops in production. The proposed conclusions determined that the main diseases that attack mango fruits are Oidio, caused by the fungus Oidio mangifera; bacterial apical necrosis, caused by the bacterium Pseudomona syringae; the floral malformation caused by the fungus Fusarium mangiferae and Anthracnose caused by the fungus Collectotrichum gloeosporioides; It is necessary to carry out preventive control of the diseases, by carrying out pruning in the plantations, using disinfected instruments and with products that manage to control or lower the incidence of the causative pathogens and also carry out biological controls with Neem-based products; Citrus extract or Trichoderma harzianum and chemical controls with fungicide products based on Captan, Benomil or Mancozeb.